Single-Grain Trace Element Geochemistry of Zircon and Monazite Large Detrital Populations from Glacial and Alluvial Sediments of Ukraine (East-European Platform) and Antarctic Peninsula (Western Antarctica): Comparison and Possible Interpretation - Savenok, S. P.; Shnyukov, S. E.; Andreev, A. V.; Morozenko, V. R. (Ukrainian Antarctic Journal, 2005)
The results of single-grain geochemical study of zircon (n = 2684) and monazite (n = 937) large detrital populations from glacial and alluvial sediments that reflect provenance within (1) the southern part of East-European Platform (EEP), including Ukrainian Shield, and (2) the subglacial area of Antarctic Peninsula (AP) in Western Antarctica are presented in the paper. Trace element (Hf, Y, Th, U, Pb etc.) content in both minerals was determined by means of special “single-grain” version of milliprobe Xray fluorescence analysis (XRF-MP/SG). “Total lead” method was used for zircon and monazite single-grain approximate age dating. Geochemical grouping of zircon grains as well as their parent rock types identification were realized on the basis of earlier suggested Hf-Y discriminant diagram. This new data set may be regarded as a representative contribution to present-day information about the crustal evolution within the both EEP and AP regions. For example a new unknown earlier stage of significant formation of monazite ( 0.50.7 Ga) was discovered. Numerous data on zircon’s single-grain geochemistry were resulted in regional-scale models of progressive growth of the Earth’s crust. Taking into account that subglacial terranes of Antarctica are inaccessible for direct study, such approach is proposed for their investigation within the project “Circum Antarctic Zircon Census” (CAZIC) in the frame of IPY 2007/2008 program.